Brønsted Acid Catalyzed Bisindolization of α‐Amido Acetals: Synthesis and Anticancer Activity of Bis(indolyl)ethanamino Derivatives. Issue 18 (6th May 2014) - Mari, Michele; Tassoni, Aurora; Lucarini, Simone; Fanelli, Mirco; Piersanti, Giovanni; Spadoni, Gilberto
Abstract: A Brønsted acid catalyzed bisindolization reaction with suitable α‐amido acetals that tolerates a wide range of indoles is reported. The method allows rapid access to the biologically relevant bisindolyl ethanamine scaffold in good to excellent yields upon mild amide basic hydrolysis. In preliminary pharmacological studies, some of these compounds display cytotoxic activity in U937 cancer cells. The marine natural alkaloid 2, 2‐di(6′‐bromo‐3′‐indolyl)‐ethylamine was the most active compound and could be a lead candidate for further optimization. For the first time, the biological role of this brominated bisindole marine alkaloid is presented. Abstract : Brønsted acid catalyzed reaction of indoles with (acylamino)acetaldehyde dimethyl acetal efficiently affords bis(indolyl)ethanamino derivatives. The dibrominated marine natural product bisindole alkaloid1 showed potent anticancer activity against U937 cells.